Relative bradycardia presented as a clinical feature of Brucella melitensis infection: A case report - Huang, Kai; Yu, Xuxia; Yu, Yushan; Cen, Yin; Shu, Jie; Yang, Naibin; Chu, Jinguo (Frontiers in Medicine, 2022)
Brucellosis, caused by Brucella species, is an infectious disease transmitted through contact with infected animals or their secretions. The clinical disease is characterized by fever and headache. Relative bradycardia is an inappropriate response of heart rate to body temperature, in which the heart rate does not increase proportionally despite a high fever. In this report, we document one case of Brucella melitensis infection demonstrating relative bradycardia. To our knowledge, this is the first report of relative bradycardia in a patient with brucellosis.